TEKNIK JOURNALING DALAM KONSELING - Zakiyah, Afifatuz (Journal of Contemporary Islamic Counselling, 2023)
Abstrak             Journaling (diary) is allow clients to express and externalize their thoughts, feelings, and expressions that are usually kept for the private internal realm. However, what makes journaling a therapeutic technique is that thid written expression is brought into counseling session and shared with the counselor openly, and becomes the driving force of the counseling. Journaling also helps keep clients focused on counseling goals when they are not in counseling session. Counseling is assistance given a counselor to the clients to solve problems. In this study, researcher used an approach of library research. In this case, the researcher “talk” a lot, “dialogues: a lot with books, archives, documents, journals, notes, statistical documentation, diaries, letters, and others. The result show that journaling technique is a technique that can help someone in directing their thoughts from the irrational to the rational. Journaling technique can help counselor in solving the client’s problem by exressing their feelings, thoughts and behaviour through writing. Keywords: Journaling Techniques, Counseling